Preserved Low-Frequency Hearing Following 20-mm Cochlear Implantation. Issue 2 (February 2015) - Brown, Kevin D.; Melton, Myles F.; Shonfield, Hannah; Kraskin, Michelle; Wolf, Jennifer
<x xml:space="preserve">Abstract</x> Objective To determine the preservation of pure tone thresholds for a series of cochlear implant patients who underwent atraumatic round window insertion with a new thin 22-mm electrode to a 20-mm depth. Study Design Retrospective, within-subject repeated measures design. Setting Tertiary care hospital. Patients Nine sequential cochlear implant patients with functional preoperative acoustic hearing (defined as low-frequency pure tone average thresholds ⩽90 dB). Intervention Therapeutic. Main Outcome Measure Pure tone thresholds after cochlear implantation. Results Low-frequency hearing preservation was achieved in all cases. Less than 10 dB average change was seen for low-frequency pure tone average measures (125, 250, 500, and 1, 000 Hz) at 6 and 12 months following cochlear implantation. Conclusions Atraumatic round window insertion with a thin 22-mm electrode to a 20-mm depth results in dramatically high levels of acoustic hearing preservation among CI patients.